2018
DOI: 10.21037/tp.2018.09.11
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric palliative care in the intensive care unit and questions of quality: a review of the determinants and mechanisms of high-quality palliative care in the pediatric intensive care unit (PICU)

Abstract: This article reviews the state and practice of pediatric palliative care (PC) within the pediatric intensive care unit (PICU) with specific consideration of quality issues. This includes defining PC and end of life (EOL) care. We will also describe PC as it pertains to alleviating children's suffering through the provision of "concurrent care" in the ICU environment. Modes of care, and attendant strengths, of both the consultant and integrated models will be presented. We will review salient issues related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…Before writing this protocol, a scoping search of the literature on systematic reviews in ICU palliative and end-of-life care was conducted. It showed that there are published systematic reviews related to types of ICUs like burns (Ribeiro et al 2023), surgical and trauma (Newsome et al 2023), cardiac (Kim et al 2022, neonatal (Abuhammad et al 2023;Kim et al 2019), pediatric (Bennett andLeBaron 2019;Howes 2015;Short andThienprayoon 2018), geriatric (Da Fonseca et al 2012;Roczen et al 2016), and cancer (Martins et al 2017). Furthermore, there were systematic reviews related to the palliative care process in ICUs that include the consults (Grabda and Lim 2021), family meetings (Singer et al 2016), eliciting preferences (Alyami et al 2019), decision-making (Johal et al 2022Oczkowski et al 2016;Spoljar et al 2020;Visser et al 2014), and communication (Schram et al 2017;Zante and Schefold 2019).…”
Section: Rationalementioning
confidence: 99%
“…Before writing this protocol, a scoping search of the literature on systematic reviews in ICU palliative and end-of-life care was conducted. It showed that there are published systematic reviews related to types of ICUs like burns (Ribeiro et al 2023), surgical and trauma (Newsome et al 2023), cardiac (Kim et al 2022, neonatal (Abuhammad et al 2023;Kim et al 2019), pediatric (Bennett andLeBaron 2019;Howes 2015;Short andThienprayoon 2018), geriatric (Da Fonseca et al 2012;Roczen et al 2016), and cancer (Martins et al 2017). Furthermore, there were systematic reviews related to the palliative care process in ICUs that include the consults (Grabda and Lim 2021), family meetings (Singer et al 2016), eliciting preferences (Alyami et al 2019), decision-making (Johal et al 2022Oczkowski et al 2016;Spoljar et al 2020;Visser et al 2014), and communication (Schram et al 2017;Zante and Schefold 2019).…”
Section: Rationalementioning
confidence: 99%
“…Additionally, some pediatric providers may be reluctant to consult PC due to fears of increasing emotional burden and diminishing parental hopes (51). However, studies support the value of the PC team as part of an interprofessional approach to the care of critically ill patients (1, 3, 52, 53). PC in the adult population with serious illness demonstrates efficacy with regard to quality of life, hospital LOS, ICU LOS, lower costs, and mortality (54, 55).…”
Section: Discussionmentioning
confidence: 99%
“…Further refinement of PC-ICU criteria and application could help standardize triggering of PC consultation and aid in optimization of timing and appropriateness across institutions. Most importantly, it is imperative that we better characterize the nature of PC involvement (timing, quantity, and quality) and further assess the impact of pediatric PC consultation, which may support equity in access to this important healthcare resource (53, 61).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the parent group scored the topic of decision-making around end of life for children admitted to PICU as the highest priority area for research (ranked sixth by HCPs). In both the United States and the United Kingdom, the most common location of pediatric death is the PICU (23,24). Many of these deaths involve withdrawal of one or more forms of life-sustaining medical treatment; therefore, discussions around end-of-life care and decision-making are clearly important both for families as well as for HCP.…”
Section: Discussionmentioning
confidence: 99%